(3GdEQg```````GH aj e`j```RGf GdTQjY```I GdESdGej``I hGdbGf```hf Gd```Ohdj GdY````Ge (B/s - (3QHj`Y SYO eMeO Ydis; (3CMeO CHh GdhaGs; (3YHO GdYRjR QeVGf Secs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3JfGhdJ LQGFe GdEQgGH aj ejRGf GdTQjYI GdESdGejI hGdbGfhf GdOhdj GdYGe hJHjf Cf GdTQjYI GdESdGejI cGf dgG GdSHb aj JfGhd gPg GdLQGFe Vef LQGFe GdMQGHI , hHjfJ eaghegG hNUGFUgG hCQcGfgG , hCf LQGFe GdEQgGH VO Cef hSde GdHTQjI GddPGf ChLHJgeG GdTQjYI GdESdGejI dOGQ GdESdGe HLejY ScGfgG HZV GdfXQ Yf Ojfge hLfSjJge hCTcGdge , hChLHJ Pdc Ydi GdEeGe Ch GdMGce (B. (3hCf GdLgGO aj GdTQjYI GdESdGejI JLGI GdeMGQHjf hGdEQgGHjjf Chdj ef LgGO GdYOh dNWQI Ydi ebGUO GdTQjYI GdESdGejI hCef hScjfI OGQ GdESdGe , hJfGhdJ GSJNOGe GdbhI GjVkG aj GdbGfhf GdOhdi GdYGe , hJfGhdJ hSGFd efY hecGaMI LQGFe GdEQgGH aj GdTQjYI GdESdGejI hGdbGfhf GdOhdj GdYGe hCSGS GdGdJRGe HefY hecGaMI gPg GdLQGFe Ke hSGFd ecGaMI LQGFe GdEQgGH aj GdTQjYI GdESdGejI hGdbGfhf GdOhdj GdYGe hcGfJ GdTQjYI GdESdGejI CTed hCYe (B- (3fXQG dNUGFUgG GdJi JJejR HgG Yf GdbGfhf GdOhdj GdYGe ef GdTehdjI hGdQHGfjI (B- (3ai hSGFd ecGaMI LQGFe GdEQgGH ShGA ef GdfGMjI GdhbGFjI HeMGQHI GSHGHgG GdSjGSjI hGdGLJeGYjI hGdGbJUGOjI hGdEYdGejI hGdOjfjI hGdJYdjejI hGdKbGajI Ch ef GdfGMjI GdYdGLjI HGbQGQ YbhHI ddeMGQHjf hGdEQgGHjjf QGOYI ddaQO hGdeLJeY hCbQJ GdeSFhdjI GdeOfjI hGdLfGFjI Ydi LQGFe GdEQgGH , ceG JfGhdJ Pdc aj GdbGfhf GdOhdj GdYGe s
It dealt with terrorism crimes in the balance of Islamic law and general international law, and it was found that Islamic law had the forefront in dealing with these crimes within the crimes of militancy , and it explained its concept, characteristics and pillars, and that terrorist crimes are against the security and peace of humanity, which were required by Islamic law for the abode of Islam with all its inhabitants, regardless of their religion and nationality And their forms, and obligated that to the imam or the ruler. And that jihad in Islamic law towards combatants and terrorists is more important than jihad against the enemy because of a threat to the purposes of Islamic law and the security and tranquility of the House of Islam, and it also dealt with the use of force in general international law, and dealt with the means of preventing and combating terrorist crimes in Islamic law and general international law and the basis of the obligation to prevent and combat these crimes, then Means of combating terrorist crimes in Islamic law and general international law The Islamic law was more comprehensive and general - due to its characteristics that distinguish it from general international law in terms of comprehensiveness and divineness - in terms of means of combating terrorist crimes, whether in terms of prevention by fighting its political, social, economic, media, religious, educational and cultural causes, or in terms of Therapeutic treatment by approving a punishment for combatants and terrorists as a deterrent to the individual and society, and it approved civil and criminal responsibility for terrorism crimes, as it dealt with in general international law.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdTQjYI GdESdGejI, (B2023 s
(3HHdjhLQGajG(B: (3UaMGJ (B423-441.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdTQjYI GdESdGejIs; (3GdeSFhdjI GdeOfjI hGdLfGFjI Ydi LQGFe GdGQgGHs; (3GdEQgGH aj ejRGf GdTQjYI GdESdGejI s; (3GdLQGFe Vef LQGFe GdMQGHIs; (3JLGI GdeMGQHjf hGdGQgGHjjfs; (3efY hecGaMI LQGFe GdGQgGH aj GdTQjYI GdGSdGejIs; (3hSGFd ecGaMI LQGFe GdGQgGHs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdTQjYI GdESdGejIs